Leaf reflectance characteristics and yield of spring oat varieties as influenced by varietal divergences and nutritional supply - Bytyqi, Bekir; Kutasy, Erika (Acta Agraria Debreceniensis, 2023)
Inadequacy of nutrients in the soil and sufficient inaccessibility to nutrients is caused by factors that affect production and productivity of spring oat varieties. Exogenous application of nutrient and real time nutrient assessment can therefore reverse these associated negative consequences. A field experiment was conducted to evaluate the response of spring oat varieties to sulphur and silicon based fertilisation. Eight spring oat varieties, four level of nutrient application was arranged in a split-plot design with three replications. The obtained results showed that foliar application of sulphur improves the grain yield of most nutrients responsive varieties by about 34.7%. However, application of silicon had shown a diminishing return association to grain yield of variety GK Kormorán, GK Pillangó, Lota, Panni. LAI, thousands grain weight, SPAD, NDVI was significantly (p < 0.05) influenced by genetic difference of the tested varieties, developmental plasticity, and nutrient application. Significantly higher grain yield was obtained from the variety Mv Pehely than the other tested varieties. Therefore, it could be inferred that a combined use of nutrient responsive spring oat varieties and sulphur containing fertilisers could be important agronomic practice to improve grain yield and to develop climate resilient oat varieties.